Escolha ocupacional e ingresso na ocupação: um estudo de fatores determinantes - França, Terezinha (1981)
This is a theoretical investigation which analizes what determines occupational choice and occupational entry. Firstly, a criticism on theoretical formulations in made, pointing out its surrounding ideology, with special emphasis on formulations of psychological n~ture. Then, it provides some reference points in order to establish an alternative theoretical reference frame. These reference points consider the individual in his wholeness, that is, the worker in his c.oncrect setting of capi talist relations of production and work. This approach recomends that emphasis on psychological aspects should not conceal economic ones and vice-versa.